Acute pancreatitis masked by diabetic ketoacidosis – case reports - Pochodowicz, Katarzyna; A. Okruszko, Michał; Szabłowski, Maciej; Bossowski, Artur; Głowińska-Olszewska, Barbara (Pediatria Polska - Polish Journal of Paediatrics, 2022)
We present 2 cases of diabetic children who developed acute pancreatitis (AP) in the course of diabetic ketoacidosis (DKA). A 14-year-old girl, diagnosed with diabetes type 1 (DT1), poorly metabolically controlled so far, was admitted with DKA. Her pancreatic enzymes were increased. In ultrasound (USG), her pancreas was enlarged. This evidence indicated AP co-existing with diabetic ketoacidosis. An 8-year-old girl, suffering from DT1, was admitted with DKA, in a diabetic coma, without verbal contact. Her pancreatic enzymes were elevated. Her pancreas was hyperechoic in USG. Criteria of AP were confirmed. DKA is a frequent severe condition occurring in children with DT1. Acute pancreatitis is a life-threatening condition. Association between AP and diabetic ketoacidosis is rare. We wish to propose with this presentation the need to check the level of pancreatic enzymes in addition to the basic tests for patients with DKA.